2007
DOI: 10.2478/s11536-007-0034-2
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment among workers occupationally exposed to excessive levels of noise

Abstract: AbstractPure tone audiometry screening and ear examinations were conducted among 138 males working as machine and equipment operators occupationally exposed to intermittent noise of 85 to 105 dBA. Hearing loss up to 30 dB (preserved socially adequate hearing) was found in 25 workers. The hearing impairment was confirmed by distortion products of otoacoustic emissions measurements. A sharp increase in the frequency of cases can be found among the workers with service length over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Hearing damage from excessive noise usually occurs at high frequencies (3, 4, and 6 kHz) and then spreads to lower frequencies (0.5, 1, and 2 kHz) which limits the working capacity and social adequacy of workers (Gidikova et al 2007;Smith 1998;Sensogut 2007). For effective noise-induced hearing loss prevention, it is important to consider the spectral content of noise as the personal protective equipment is often designed according to the noise spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Hearing damage from excessive noise usually occurs at high frequencies (3, 4, and 6 kHz) and then spreads to lower frequencies (0.5, 1, and 2 kHz) which limits the working capacity and social adequacy of workers (Gidikova et al 2007;Smith 1998;Sensogut 2007). For effective noise-induced hearing loss prevention, it is important to consider the spectral content of noise as the personal protective equipment is often designed according to the noise spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Gidikova et al had found faster increment of hearing impairment frequency among the workers who served less than 10 years (about 5.45%). Whereas workers who served more than 10 years had gradual increment of hearing impairment frequency (about 26.5%) because of increasing noise exposures duration 17 ) . ACOEM also men-tioned NIHL usually occurs slowly and has the highest frequency of occurrence during the first 10-15 years of noise exposure duration.…”
Section: Occupational Noise Exposurementioning
confidence: 96%
“…In addition, for most machines octave bands with an elevated value of L eq are very wide, with maximum levels at high frequencies with the most dominant noise at 5000 Hz, whereas for the wood, metal and energy industries the most dominant noise was observed at mid frequencies (500-2000 Hz). Since hearing damage from excessive noise primarily occurs at high frequencies (3, 4, and 6 kHz) and then spreads to lower frequencies, working capacity and social adequacy of workers is limited (Gidikova et al, 2007). In addition, knowing that double increase of the sound pressure increases the level of noise for 3 dB(A), it can be rightly concluded that the situation gets worse with an increasing number of machines.…”
Section: Db(a)mentioning
confidence: 99%